(untitled) (Hematology Meeting Reports, 2009)
Zoledronic acid (Zol) is the most potent aminobisphosphonate (ABP) currently available to treat bone disease in cancer patients. Zol specifically targets the mevalonate (MEV) pathway of osteclasts precursors and mature osteoclasts. By inhibiting the farnesyl pyrophosphate (FPP) synthase, Zol prevents the generation of FPP and geranylgeranylpyrophosphate (GGPP) that are essential compounds to prenylate proteins like Ras and Rho among others. The accumulation of unprenylated proteins in osteoclast precursors and mature osteclasts prevents their differentiation and activation and ultimately leads to cell death by apoptosis.